2020
DOI: 10.1111/febs.15224
|View full text |Cite
|
Sign up to set email alerts
|

Energy landscape of domain motion in glutamate dehydrogenase deduced from cryo‐electron microscopy

Abstract: The EM maps of the four conformations were deposited to Electron Microscopy Data Bank (EMDB) as accession codes EMD-9845 (open), EMD-9846 (half-open1), EMD-9847 (half-open2), and EMD-9848 (closed), respectively. In addition, the structural models built for the Abbreviations AFM, atomic force microscopy; core domain, core domain engaging in hexamer formation; cryoEM, cryo-electron microscopy; FSC, Fourier shell correlation; GDH, glutamate dehydrogenase; GS-FSC, gold-standard Fourier shell correlation; MD, molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 72 publications
2
47
0
Order By: Relevance
“…Nonetheless, the conformational energy landscape proposed for T. profundus GDH is unbiased by crystal contacts that might favor some conformations more than others. On the other hand, flash-cooling may introduce other types of bias, as the authors acknowledge (Oide et al, 2020). It is also important to note that the conformational dynamic of T. profundus GDH was observed in the absence of NAD(P) or substrate/product.…”
Section: The Dynamics Of the Coenzyme Binding Domain IImentioning
confidence: 92%
See 1 more Smart Citation
“…Nonetheless, the conformational energy landscape proposed for T. profundus GDH is unbiased by crystal contacts that might favor some conformations more than others. On the other hand, flash-cooling may introduce other types of bias, as the authors acknowledge (Oide et al, 2020). It is also important to note that the conformational dynamic of T. profundus GDH was observed in the absence of NAD(P) or substrate/product.…”
Section: The Dynamics Of the Coenzyme Binding Domain IImentioning
confidence: 92%
“…A very recent cryo electron microscopy (cryo-EM) study of Thermococcus profundus GDH further highlighted the dynamics of the GDH machine (Oide et al, 2020). The authors found a broad range of domain II conformations.…”
Section: The Dynamics Of the Coenzyme Binding Domain IImentioning
confidence: 99%
“…Recently, we began cryogenic TEM observations of phot2 [ 43 ]. Cryogenic TEM can classify images of heterogeneous structures of proteins caused by chemical modification, intrinsic molecular motions, and/or BL-induced conformational changes [ 78 ]. However, the stabilization buffer of phot2 used in SAXS experiments is unsuitable for cryogenic TEM observation of frozen-hydrated phot2 because of the high concentrations of NaCl and glycerol.…”
Section: Discussionmentioning
confidence: 99%
“…While the above achievements deserve praise, the full potential of electron microscopy as a technique remains veiled. EM can image multiple states of a protein simultaneously, which can be resolved and placed in an energetic landscape [16,17]. More importantly, sample preparation allows a broad range of specimens to be imaged, allowing for the structural determination of proteins from natural sources.…”
Section: Of 14mentioning
confidence: 99%